Induction of changes by nitrification inhibitor and nitrogen source on vegetative growth, physiological processes and biochemical constituents of Kinnow mandarin - DHAKAR, M K; SINGH, A K; SINGH, S K; PATEL, V B; PAL, MADAN (The Indian Journal of Agricultural Sciences, 2017)
A field experiment was conducted on two-year-old Kinnow mandarin plant to find out effect of different nitrogen sources and nitrification inhibitors on vegetative growth, physiological processes and biochemical constituents of Kinnow mandarin. There were thirteen treatments comprising four nitrogen sources, viz. ammonium sulphate (AS), calcium nitrate (CN), mixture of ammonium sulphate + calcium nitrate and urea, two nitrification inhibitor, viz. Dicyandiamide (DCD) 5% of fertilizers, meliacins (M) 0.1% of fertilizers and control. The increase in tree height was recorded significantly higher in plants treated with AS + DCD (44.05%); whereas, tree spread E-W (77.33%), tree spread N-S (66.03%), specific leaf area (123.86 cm2/g) and shoot growth rate (247.39%) was found maximum in AS + M. In the plants applied with AS + DCD registered significantly maximum values of chlorophyll (a, b and total) content, photosynthetic rate and stomatal conductance. However, transpiration rate was found maximum under treatment AS + M when applied during winter and summer in split doses. Ammonium sulphate treated with DCD produced statistically highest total soluble sugar (9.22, 9.78 and 9.40% leaf fresh wt) and soluble proteins (74.80, 76.49 and 71.96 mg/g leaf dry wt) during winter, autumn and summer, respectively followed by ammonium sulphate treated with meliacins. The ammonium sulphate and urea as source of N along with nitrification inhibitor have a strong impact on growth and physio-biochemical parameters on Kinnow plants; thus, improved the performance of Kinnow plants under above natural pH soil conditions.